Proposals for developing the Standards and Procedures Guide for Accrediting Primary and Secondary Schools (Second Edition) in Accordance with Regular and Extraordinary Pupils and (Students An analytical study of the content of the document) (Journal of Human Sciences, 2025)
The current research aims to modify and develop the standards and indicators of the quality of educational programs provided to primary and secondary education institutions for the Standards and Procedures for Accrediting Public and Private Primary and Secondary Schools (2020) Manual, the second edition issued by the National Centre for Quality Assurance and Accreditation of Educational and Training Institutions in Libya, in a manner that suits the category of regular and extraordinary students and pupils, which contains seven standards containing (130) indicators, and the researcher adopted the content analysis method in it, due to its suitability to the nature of the subject, and on the other hand, it is a research method for describing and analysing any scientific content, document or guide objectively, and identifying all strengths and weaknesses, in order to obtain conclusions that contribute to developing a proposal or idea. Through analysing the content of the document, the researcher did the following:-               Identifying the strengths and weaknesses of the document in general.-               Identifying the strengths and weaknesses of each of the seven standards in general and their indicators in particular.-               Proposing the development, improvement and addition of what is deemed appropriate for those standards and indicators in a manner that is appropriate for the category of regular and extraordinary students and pupils.